THE EFFECT OF CONSUMER CONFUSION ON BRAND LOYALTY ON LOW INVOLVEMENT PRODUCT CATEGORY - Tamburian, Christian (FEB Universitas Sam Ratulangi Manado, 2013)
Consumer confusion has become an ever increasing problem as the rapid global market developments, lead consumers to receive a lot of information nowadays. Consumer confusion, which is caused by product similarity, choice and/or information overload, and the presence of ambiguous information, can negatively affect consumers’ decision making and in fact consumers’ brand loyalty, thereby also companies’ profitability. The purpose of this quantitative study is to investigate how the three variables (i.e. similarity, overload, ambiguity) of Walsh et al.ʼs (2007) consumer confusion proneness model affect consumers’ brand loyalty, concerning low involvement products. A conceptual framework based on consumer behavior and consumer confusion literature was utilized to form 4 hypotheses predicting the causality between the different variables. After validating and adapting the scale to data gathered through questionnaires regarding 100 consumers’ purchasing habits of tooth paste, an analysis of the method multiple regressions revealed that none of the alternative hypothesis was accepted. However there is a relationship on the similarity confusion and brand loyalty variable, even though it is not significant but since the sign is negati as the theoretical expectations, there is an increase in similarity confusion that causes a decrease in brand loyalty. All implications are discussed, concluding with possible limitations and recommendations for further researches. Keywords: consumer confusion, brand loyalty